A Young Woman with Ischemic Stroke: Should We Pay More Attention to Varicella Zoster Infection? - Cláudia Borbinha; João Pedro Marto; Sofia Calado; Miguel Viana-Baptista (Case Reports in Neurology, 2016)
Ischemic and hemorrhagic stroke are recognized complications of Varicella zoster virus (VZV) infections, although uncommon and poorly documented. The authors report the case of a 31-year-old woman admitted with acute ischemic stroke of the right posterior cerebral artery and a history of a thoracic rash 1 month before. Aspirin and simvastatin were prescribed, but the patient suffered a stepwise deterioration the following days, with new areas of infarction on brain imaging. Despite no evidence of cardiac or large vessel embolic sources, anticoagulation was started empirically 6 days after stroke onset. One week later, symptomatic hemorrhagic transformation occurred. The diagnosis of VZV vasculopathy was then considered, and treatment with acyclovir and prednisolone was started with no further vascular events. Cerebrospinal fluid analysis and digital subtraction angiography findings corroborated the diagnosis. The patient was discharged to the rehabilitation center with a modified Rankin scale (mRS) score of 4. On the 6-month follow-up, she presented only a slight disability (mRS score 2). In conclusion, VZV vasculopathy needs to be considered in young adults with stroke. A high index of suspicion and early treatment seem to be important to minimize morbidity and mortality. Anticoagulation should probably be avoided in stroke associated with VZV vasculopathy.